2014
DOI: 10.2337/db13-1855
|View full text |Cite
|
Sign up to set email alerts
|

Defects in β-Cell Ca2+ Dynamics in Age-Induced Diabetes

Abstract: Little is known about the molecular mechanisms underlying age-dependent deterioration in β-cell function. We now demonstrate that age-dependent impairment in insulin release, and thereby glucose homeostasis, is associated with subtle changes in Ca2+ dynamics in mouse β-cells. We show that these changes are likely to be accounted for by impaired mitochondrial function and to involve phospholipase C/inositol 1,4,5-trisphosphate–mediated Ca2+ mobilization from intracellular stores as well as decreased β-cell Ca2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 53 publications
1
32
2
Order By: Relevance
“…Diabetic predisposition and added risk factors and epigenetic regulation, however, may trump the resiliency of the beta cell (9,42). Our study now shows that the islet as an organ seems to be threatened by factors that affect vascular function.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Diabetic predisposition and added risk factors and epigenetic regulation, however, may trump the resiliency of the beta cell (9,42). Our study now shows that the islet as an organ seems to be threatened by factors that affect vascular function.…”
Section: Discussionmentioning
confidence: 66%
“…Age-dependent dysfunction of islets and the concomitant dysregulation of blood glucose levels increase the risk for type 2 diabetes (1), which in turn contributes to other age-related chronic diseases. In general, it has been assumed that aging causes an intrinsic dysfunction of the insulin-secreting beta cells through reduced proliferative capacity and/or defective insulin secretion (1)(2)(3)(4)(5)(6)(7)(8)(9). However, there have been numerous reports that age-dependent impairment of glucose homeostasis is not just a result of intrinsic, age-dependent dysfunction of islets but is also caused by systemic factors.…”
mentioning
confidence: 96%
“…GJ coupling between β-cells is essential for islet function. 6,86 The strength of this coupling decreases with age 87,88 and in animal models of diabetes. 89,90 Therefore, our simulations predict that a reduction in GJ coupling would reduce the ability of hubs to generate whole-islet Ca 2+ oscillations, greatly impairing insulin output.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been reported that non-oscillatory islets under glucose stimulation display a defect in ER Ca 2+ homeostasis and higher [Ca 2+ ] c compared to oscillatory islets, indicating that the ER defect might also be an early marker of islet dysfunction [329]. In addition, aging was shown to impair both Ca 2+ uptake and Ca 2+ release from the ER in mouse ␤-cells [330].…”
Section: Impact On [Ca 2+ ] Er Changesmentioning
confidence: 97%
“…Similar defaults in [Ca 2+ ] c handlings were observed in obese diabetic db/db mice, Ca 2+ changes were also decreased and delayed in response to glucose [325,326], with an early disappearance of Ca 2+ oscillations [327], and in diabetic fatty rats (ZDF) due to a decreased expression of the ␣1 subunit of the L-type Ca 2+ channels, and a subsequent reduction of Ca 2+ influx [328]. Importantly, the alteration of [Ca 2+ ] c oscillations in ␤-cells were reported to be an early marker of islet dysfunction [329], and to occur more frequently in aged islets due to a progressive decline of mitochondrial function [330]. Additionally, both incretins Gastric Inhibitory Polypeptide (GIP) and GLP-1 were recently reported to induce synchronous rise in [Ca 2+ ] c in human islets, while this Ca 2+ signal became asynchronous in FFAs treated islets [78].…”
Section: Impact On [Ca 2+ ] C Changesmentioning
confidence: 99%